Perlindungan Hukum Terhadap Hak-Hak Nelayan Tradisional Dalam Zona Ekonomi Eksklusif : Studi Di Pulau Maringkik - Lestari, Aprianun; H. Arba (Faculty of Law, University of Mataram, 2024)
The research aims to determine the rights of traditional fishing communities in the exclusive economic zone on Maringkik Island and to determine the implementation and legal protection of the rights of conventional fishermen in carrying out their business in the exclusive economic zone. This type of research is empirical legal research using statutory, conceptual, and sociological approaches. The results of this research are that legal regulations regarding the rights of traditional fishermen in the exclusive economic zone on Maringkik Island are regulated in customary regulations, namely nyelmatan dilaok and statutory regulations, among others, law number 5 of 1983 concerning exclusive economic zones, laws number 31 of 2004 regarding changes to law number 45 of 2009 concerning fisheries, and law number 7 of 2016 concerning the protection and empowerment of fishermen, fish farmers, and salt farmers as well as other related regulations. Traditional fishermen have certain rights in carrying out business, one of which is the right to catch and keep fish. The right to catch and keep fish on Maringkik Island still uses rules set by the community, passed down from generation to generation. Implementing legal protection based on relevant laws and regulations is still not done well.